The Effect of PDEODE Learning Model on Competency of Electronic and Electronic Basics Lessons Reviewed From The Ability of Formal Reaching Students of Class X TITL A In Raden Rahmat Mojosari Vocational School - Hidayati, Ayu Zulaikha; Basuki, Ismet; Buditjahjanto, IGP Asto (Universitas Malikussaleh, 2019)
Improving student competence is very dependent on the learning model and students' formal reasoning abilities. This study aims to: (1) analyze differences in competencies between students taught with the PDEODE learning model and students taught using direct learning models in DLE subjects at SMK Raden Rahmat Mojosari, (2) analyze differences in competencies between students who have TKPFT and students who have TKPFR on DLE subjects at SMK Raden Rahmat Mojosari, (3) analyze the interaction between the use of learning models and TKPF on student competencies on DLE subjects at SMK Raden Rahmat Mojosari. This research is a type of experimental research that uses factorial analysis design. Data collection instruments were in the form of passive component social attitude competency observation sheets, passive component knowledge competency test sheets, passive component skills competency performance test sheets and formal reasoning ability test sheets for students. Based on the results of the study, it can be concluded that: (1) there are differences in competencies between students taught using the PDEODE learning model and students taught using direct learning models in DLE subjects at SMK Raden Rahmat Mojosari, (2) there are differences in competencies between students who have TKPFT and students who have TKPFR on DLE subjects at SMK Raden Rahmat Mojosari, (3) there is an interaction between the use of learning models and TKPF on student competencies in DLE subjects at SMK Raden Rahmat Mojosari.